1996
DOI: 10.1097/00002820-199608000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personal message with music on anxiety and side effects associated with chemotherapy

Abstract: The purpose of this pilot study was to evaluate the benefits of a message from a patient's physician audiotaped over music on reducing anxiety and side effects of patients receiving chemotherapy. A convenience sample of 97 adult patients receiving chemotherapy for the first time was assigned to either an experimental or control group. Before beginning the first chemotherapy treatment, all subjects completed a demographic questionnaire and the Spielberger State Anxiety Inventory (SSAI). Participants in the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 6 publications
1
38
0
5
Order By: Relevance
“…Music has been used therapeutically in hospice [8,11,10], in palliative care [5, 14-19, 24, 25], while receiving radiation therapy [27], during chemotherapy [17,23,[27][28][29], and undergoing medical procedures (such as port placement/removal or tissue biopsy) [12,20]. Music has been used in symptom management such as for pain [2, 10-14, 16, 30, 34] and anxiety [1,2,11,12,14,16,23,27,30] and has been associated with improved quality of life [5,9] and spiritual healing [14,19,21,25,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Music has been used therapeutically in hospice [8,11,10], in palliative care [5, 14-19, 24, 25], while receiving radiation therapy [27], during chemotherapy [17,23,[27][28][29], and undergoing medical procedures (such as port placement/removal or tissue biopsy) [12,20]. Music has been used in symptom management such as for pain [2, 10-14, 16, 30, 34] and anxiety [1,2,11,12,14,16,23,27,30] and has been associated with improved quality of life [5,9] and spiritual healing [14,19,21,25,30].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trials measuring the benefits of music therapy are less common. In reviewing the literature, only 15 studies [1,3,4,6,7,9,10,12,20,23,24,[27][28][29][30] included objective measurement of music therapy effectiveness with cancer patients. Therefore, we have sought to add this to the quantitative literature in this study.…”
Section: Introductionmentioning
confidence: 99%
“…These interventions have focused on muscle relaxation as well as on breathing exercise [31,33,55,69] with the belief that relaxation can prevent side effects and treatment-related anxiety [6,17,43,45,65]. Furthermore, relaxation can be seen as a means of achieving psychological and psychosocial goals (coping, counteracting stress, depression and anxiety) [6,14,17,55,63,65]. Similarly, sports science and psychology have shown that training in body awareness can be used by athletes to release tension and to control anxiety [53,66].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative Studien untersuchten unter anderem die unterstützende Wirkung rezeptiver Musik bei krankheitsbedingten Einschlafstörungen [13] und die Adjuvanz der medizinischen Therapie chronischer Krebsschmerzen [14][15][16]. Einige Studien [17,18] fanden einen positiven Einfluss von Musik auf Ängste und depressive Gestimmtheit während der Verabreichung einer Chemotherapie [3]. Zur Klangwirkung und Verwendung des Monochords in der Musiktherapie finden sich vornehmlich im deutschsprachigen Raum Veröffentlichungen [19,20].…”
Section: Introductionunclassified